Serum Biomarkers of Endothelial Dysfunction in Fabry Associated Cardiomyopathy - Loso, Jefferson; Lund, Natalie; Avanesov, Maxim; Muschol, Nicole; Lezius, Susanne; Cordts, Kathrin; Schwedhelm, Edzard; Patten, Monica (Frontiers in Cardiovascular Medicine, 2018)
Background: Fabry disease (FD) is characterised by early development of vasculopathy and endothelial dysfunction. However, it is unclear whether these findings also play a pivotal role in cardiac manifestation. As Fabry cardiomyopathy (FC) is the leading cause of death in FD, we aimed to gather a better insight in pathological mechanisms of the disease. Methods: Serum samples were obtained from 17 healthy controls, 15 FD patients with and 7 without FC. FC was defined by LV wall thickening of > 12 mm and elevated proBNP and/or high sensitive Troponin T (hsT) values. A multiplex ELISA-Assay for 23 different angiogenesis markers was performed in pooled samples. Markers showing significant differences among groups were further analysed in single samples using specific Elisa antibody assays. L-homoarginine (hArg), L-arginine, asymmetric (ADMA) and symmetric Dimethylarginine (SDMA) were quantified by liquid chromatography - mass spectrometry. Results: Angiostatin and matrix metalloproteinase 9 (MMP-9) were elevated in FD patients compared to controls independently of the presence of FC (angiostatin: 98 ± 25 vs. 75 ± 15 ng/mL; p = 0.001; MMP-9: 8.0 ± 3.4 vs. 5.0 ± 2.4 µg/mL; p = 0.002). SDMA concentrations were highest in patients with FC (0.90 ± 0.64 µmol/l) compared to patients without (0.57 ± 0.10 µmol/l; p = 0.027) and vs. controls (0.58 ± 0.12 µmol/l; p = 0.006) and was positively correlated with indexed LV-mass (r = 0.61; p = 0.003), hsT (r = 0.56, p = 0.008) and lyso-Gb3 (r = 0.53, p = 0.013). Accordingly, the ratio of L-homoarginine to SDMA (hArg/SDMA) was lowest in patients with FC (2.63 ± 1.78) compared to controls (4.16 ± 1.44; p = 0.005). For L-arginine, hArg and ADMA no significant differences among groups could be detected, although a trend towards higher ADMA and lower hArg levels could be observed in the FC group. Furthermore, a significant relationship between kidney and cardiac function could be revealed (p = 0.045). Conclusion: Elevated MMP-9 and angiostatin levels suggest an increased extracellular matrix turnover in FD patients. Furthermore, endothelial dysfunction may also be involved in FC, as SDMA and hArg/SDMA are altered in these patients.